2017
DOI: 10.18632/oncotarget.21871
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epithelial-mesenchymal transition and metastasis by TGF-β, P-bodies, and autophagy

Abstract: Processing bodies (P-bodies) are ribonucleoprotein complexes involved in post-transcriptional mRNA metabolism that accumulate in cells exposed to various stress stimuli. The treatment of mammary epithelial cells with transforming growth factor-beta (TGF-β), triggers epithelial-mesenchymal transition (EMT), and induces the formation of P-bodies. Ectopic expression of the transcription factor TWIST, which stimulates EMT downstream of the TGF-β receptor, also promotes P-body formation. Removal of TGF-β from treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 47 publications
(56 reference statements)
4
57
0
Order By: Relevance
“…Mesenchymal cells also have an increased capacity to persist in the presence of chemotherapy (4,35,36). Our previous studies and our data herein are consistent with the notion that autophagy drives the MET process and efficient progression to macroscopic tumor formation (15). Our findings are strongly supported by recent studies indicating autophagy facilitates a dormant-to-proliferative switch by tumor cells within the lungs (16).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Mesenchymal cells also have an increased capacity to persist in the presence of chemotherapy (4,35,36). Our previous studies and our data herein are consistent with the notion that autophagy drives the MET process and efficient progression to macroscopic tumor formation (15). Our findings are strongly supported by recent studies indicating autophagy facilitates a dormant-to-proliferative switch by tumor cells within the lungs (16).…”
Section: Discussionsupporting
confidence: 92%
“…We have recently demonstrated that induction of EMT by TGFb induces the formation of cytoplasmic RNA-processing complexes called P-bodies, and clearance of P-bodies through autophagy is required for reversal of EMT (15). On the basis of our previous identification of a role for SYK in promoting stress granule clearance through autophagy and our identification of multiple P-body proteins as SYK substrates, we next sought to assess a role for SYK in P-body formation and clearance (11,27).…”
Section: Syk Is Present In P-bodies and Facilitates Their Clearance Dmentioning
confidence: 99%
See 2 more Smart Citations
“…In both development and disease, post-transcriptional regulation and, in particular, RNA turnover are key mechanisms by which cells are able to quickly alter their transcriptomic landscape and transit between cell states (Chen and Shyu, 2017;Hardy et al, 2017;Lou et al, 2015). The process of RNA decay is highly conserved across eukaryotes and mediated by multiple mRNA turnover pathways (Parker and Song, 2004).…”
Section: Introductionmentioning
confidence: 99%